Asam Laktat Hasil Fermentasi Limbah Kubis Menghambat Angka Lempeng Total dan Mempertahankan Kualitas Fisik Ikan Segar - Yosephina Ardiani S; M Fadhil (VISIKES: Jurnal Kesehatan Masyarakat, 2017)
Fish is a food that is consumed by many people, but fish quickly rot due to the activity of microorganisms so that it can be classified into high perishable food groups. Fish preservation can be done by natural preservation using lactic acid fermented cabbage. The purpose of the study was to determine the concentration of lactic acid most effective against the total plate number and physical quality of fresh fish. This was an experimental research. The purposivesamplng technique was use to find fresh fish from the place of fish auction in the Cirebon city. The Sample weight is 100 - 200 grams. The three lactic acid concentrations were used in this study: 15%, 20% and 25%. The total data of germs measured by laboratory tests and physical quality was carried out by organoleptic tests. Bivariate analysis was used to determine the effect of lactic acid on total plate numbers using the One way Anova test and the effect of lactic acid on physical quality was analyzed using the Friedman Test. There was a significant difference between the concentration of lactic acid solution to the total plate number of fresh fish. The 25% lactic acid concentration can reduce the total plate number below the threshold value. The concentration of lactic acid solution does not affect the taste, color and texture of fresh fish and affects the aroma or smell of fresh fish.Keywords: lactic acid, cabbage, fresh fish quality